iPad for seniors - Spivey, Dwight (--For dummies., 2022)
iPads are some of the coolest and most versatile tablets on the market today. You can watch movies, listen to music, go online, talk to your family and friends, and pretty much anything else you can think of. But with updates coming all the time, it can be difficult to keep track of the smorgasbord of features this portable device offers. That's where iPad For Seniors For Dummies comes in! This handy guide to the even handier iPad has all the latest updates for the newest version of the famous tablet and its operating system. Want to talk to Siri? Check this guide. Want to find where those cute photos of your grandkids went? We've got you covered. Perfect for anyone who just got a new iPad as a gift, or for anyone who's got an existing iPad kicking around that they've been meaning to use more often, iPad For Seniors For Dummies is the easy-to-follow and step-by-step tutorial you've been looking for.